Intellectual property system with a heart? Patents and public health in Malaysia and some Asean countries - Abdul Ghani Azmi, Ida Madieha (Sweet & Maxwell Asia, 2011)
Patents play a vital role in facilitating the creation of inventions to improve human life through the development of new medicines, medical products and equipment. Despite that patents have often been accused of being anti development especially in the context of patented drugs. Patented drugs are mostly more expensive than generic drugs and thus have been alleged to be not widely accessible to the public. National and global patent laws contain derogations from the strict rules for public health reasons. TRIPS allow the issuance of compulsary licences and and government use in the case of national emergency. Parallel imports are also allowed to enable the cheapest (original) drugs to be imported. Patents are by nature limited by duration, i.e. 20 years from the date of application, after which the drug falls into the public domain. Research exceptions could be found in many national countries' legislation. Patents are also territorial in nature and many drugs are deliberately not patented in some ASEAN contries, giving the room for these countries to produce cheaper drugs. This paper explores the limitations and flexibilities under the patent system in selected ASEAN countries which could be used as a support system for public health. The provisions explored will be those relating to : (1) Bolar provision/Regulatory approval (2) Scientific Research Exceptions (3) Compulsary licence (4) Government use (5) Parallel imports In addition, several other provisions critical to public health are examined. They are as follows: (1) Clinical data provision (2) Patent extension terms (3) Paragraph 6 system (4) Other relevant exceptions The countries chosen are Singapore, Malaysia, Vietnam, Indonesia and Thailand.